2020
DOI: 10.1021/acs.chemrestox.9b00483
|View full text |Cite
|
Sign up to set email alerts
|

Crossing Biological Barriers by Engineered Nanoparticles

Abstract: Engineered nanoparticles (ENPs) may cause toxicity if they cross various biological barriers and are accumulated in vital organs. Which factors affect barrier crossing efficiency of ENPs are crucial to understand. Here, we present strong data showing that various nanoparticles crossed biological barriers to enter vital animal organs and cause toxicity. We also point out that physicochemical properties of ENPs, modifications of ENPs in biofluid, and physiological and pathological conditions of the body all affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 64 publications
0
27
0
1
Order By: Relevance
“…Maternal intrauterine inflammation significantly increased the maternal-fetal transfer of Au NPs (3 nm and 13 nm) [120]. Finally, secondary modifications of NPs by biofluid components, such as the formation of protein corona, affected the placental transfer of NPs [124,131].…”
Section: Maternal-fetal Np Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal intrauterine inflammation significantly increased the maternal-fetal transfer of Au NPs (3 nm and 13 nm) [120]. Finally, secondary modifications of NPs by biofluid components, such as the formation of protein corona, affected the placental transfer of NPs [124,131].…”
Section: Maternal-fetal Np Transfermentioning
confidence: 99%
“…Previous studies demonstrated that CB NPs, CNTs, PS NPs, Si O 2 NPs [118], TiO 2 NPs [118], ZnO NPs [11,48], ZrO 2 NPs [18,119], CeO 2 NPs, Au NPs [120][121][122], Ag NPs, and quantum dots (QDs) [15,123] could cross the placental barrier and induce fetotoxicity. Properties of NPs, maternal conditions, exposure schedule, and modification of NPs by biofluid components affected the placental transfer efficiency of NPs [124,125].…”
Section: Maternal-fetal Np Transfermentioning
confidence: 99%
“…35 The increase in circulation time has two effects: on the one hand it allows for higher accumulation of the nano-carriers on the site of the diseased tissue, while at the same time it increases the likelihood of crossing biological barriers and accumulating vital organs, thus increasing non-selective toxicity. 36…”
Section: A Nanotoxicitymentioning
confidence: 99%
“…Enhanced permeability and retention of nanoparticles can account for >20% increase in nanoparticle accumulation compared to healthy organs [ 94 ]. On the other hand, complications of human diseases, such as fibrosis and aberrant circulation, can markedly reduce blood flow and the access of nanoparticles to organs [ 95 ].…”
Section: Extracellular Vesicles (Ev) As Drug Delivery Vehiclesmentioning
confidence: 99%